Effect of delayed graft function on immediate and long-term kidney transplant outcomes - A. V. Shabunin; P. A. Drozdov; I. V. Nesterenko; D. A. Makeev; S. A. Astapovich; O. S. Zhuravel; L. R. Karapetyan (Вестник трансплантологии и искусственных органов)
Objective: to analyze the immediate and long-term outcomes of kidney transplantation (KT) depending on the duration of delayed graft function (DGF). Materials and methods. The study conducted a retrospective analysis of KT outcomes in 312 patients operated on at Botkin Hospital from June 2018 to December 2022. Exclusion criteria were primary non-function, severe surgical complications that required emergency transplantectomy in the first week after KT and cases where a comprehensive approach to DGF prevention was applied. DGF was defined as the need for dialysis within the first 7 days of KT. The severity of this complication was assessed by the time it took the transplanted kidney function to normalize from mild DGF to severe. We analyzed the immediate and long-term outcomes of KT depending on the presence of initial function and the severity of DGF. Results. DGF developed in 25.3% of cases. The mean time for graft function normalization was 16.5 ± 6.8 days. Mild DGF occurred in 68% of cases, severe DGF was determined in the remaining cases (32%). The incidence of complications was statistically significantly higher in the severe DGF group: 14/25 (56%) vs. 15/54 (27.8%) (p = 0.047). There were also no significant differences in the rate of complications between recipients with immediate and mild DGF: 43/233 (18.4%) vs. 15/54 (27.8%) (p > 0.05). Severe DGF lasting for more than 2 weeks had a statistically significant association with postoperative complications (p = 0.047) and with decreased long-term graft survival (log-rank p = 0.021). Conclusion. Development of severe DGF mainly depends on donor characteristics, timing and peculiarities of graft preservation. Nevertheless, other factors, such as acute calcineurin inhibitor nephrotoxicity, should not be ignored. Therefore, prevention of all potentially modifiable risk factors for DGF should go hand in hand with the expansion of the indications for donation.